Building Islamic Morality Partnership With Gen-Z in Business Performance - Sinar Hubtriyan Ade; Rokhmad Budiyono; Edy Purwanto; Bagus Yunianto Wibowo (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Focusing on relationships and collaborations as a research imperative, this study analyzes batik micro, small, and medium-sized enterprises (MSMEs) owned by Generation Z in Central Java, Indonesia. This study introduces an innovative concept, the Islamic Morality Partnership, to enhance relationship quality in business performance, thereby addressing the empirical gap between relational capital and commercial performance. This study aims to investigate how Personal Openness and Personal Reputation contribute to the development of Islamic Morality Partnership and Relationship. The impact of the Islamic Morality Partnership on relationship quality and the relationship quality on business results, in addition to quality. The participants in this study were 100 batik MSME business owners from Generation Z in Central Java, Indonesia. The Path Analysis technique was employed with SEM software (LISREL) to analyze data collected through surveys of batik MSME owners from Generation Z. According to the findings, MSME owners from Generation Z who possess a high degree of Personal Openness are considerably better able to form Islamic moral partnerships. Islamic Morality Equality, Islamic Morality Mutual Benefit, and Islamic Morality Sustainability are the defining characteristics. On the other hand, the development of moral collaborations and the quality of relationships are unaffected by one's personal reputation. Additionally, it has been demonstrated that Islamic Morality Partnerships have a significant impact on relationship quality, which in turn leads to better business outcomes for batik MSMEs owned by Generation Z. In conclusion, a company's success depends more on the caliber of its relationships and partnerships based on Islamic values than on the owner's public image alone. As a result, strategies for promoting ethical relationships and enhancing relationship quality are essential components of Islamic Marketing and Relationship Marketing